Experimental study on the residual stresses of 800 MPa high strength steel welded box sections. (September 2018) - Cao, Xianlei; Xu, Yong; Wang, Min; Zhao, Geng; Gu, Lixiang; Kong, Zhengyi
Abstract: This study presents the residual stresses magnitude and distribution of 800 MPa high strength steel welded box sections. The value of residual stresses is investigated using a method of sectioning, and the effect of width to thickness ratio on the magnitude of stresses is considered in the analysis. From the results of experiment, the influence of width to thickness ratio on the tensile residual stresses in welded zone is small, while the effect of width to thickness ratio on the compressive residual stresses located in the center of plates is large. The maximum tensile residual stresses values change from 0.30 fy to 0.56 fy, and the constant compressive stresses ranges from 0.06 fy to 0.26 fy . The residual stresses distributed in all cross-section satisfies the self-balancing requirement. Comparison of distribution and magnitude of residual stresses between test data and existing models are made. A simplified model is suggested to estimate the residual stresses distribution of steel welded box section made of 800 MPa high strength steel. Highlights: The effect of the width to thickness of plates on the residual stresses is established. The residual stresses in all sections is in self-equilibrium. A simplified model for 800 MPa HSS welded box sections is suggested.